Análise paleomagnética da Formação Cerro Negro, Grupo La Providencia (Ediacarano, Argentina) - Papel, Manoela Machado [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The Neoproterozoic area in Argentina is relatively restricted and there is a considerable lack of data on the accuracy of the age of the local sedimentary rocks and the paleogeography of the depositional environments. The apparent migration of the magnetic poles, which defines the position of the plates in time, is well documented for Gondwana in the period between 550-500 Ma, but there is a scarcity of such data in the interval between 600-550 Ma. A paleomagnetic analysis of the Cerro Negro Formation, La Providencia Group, Argentina, Ediacaran, can contribute to the paleomagnetic knowledge of this interval. Three rock collections, one outcrop (CA) and two cores (TSE-13 and TA-21) were studied. Three components were isolated in each set of samples, named A, B and C. The low stability A component of the three collections shows a large dispersion of data and, therefore, unreliable statistical results with high errors. The B componente, very widespread, is considered secondary, resulting from remagnetization processes between Permian and Triassic. In CA collection, the B component, unlocked at temperatures around 350 °C, shows mean direction Dec: 356.2, Inc: -9.7 (n: 17 and α95: 9.3). In TSE-13 collection, component B reveal demagnetizing temperatures ≤350 °C, with mean direction Dec: 8.9, Inc: -37.4 (n: 21 and α95: 10.4). In TA-21, dual-polarity component B, with unblocking temperatures ≤625 °C, shows mean direction Dec: 8.1, Inc: -50.7 (n: 46 and α95: 6.3). The C component of the TA-21 core, also establish secondary, with dual-polarity and demagnetization temperatures ≤675 °C, shows Dec: 12.2, Inc: -38.7 (n: 61 and α95: 4.7). The C component of the TSE-13 collection was the only isolated component that carries the characteristic magnetization of the rocks, transported by hematite (temperatures between 600-675 °C), with Dec: 40.4, Inc: 45.0 (n: 9 and α95: 12.3). The results of remagnetized samples can not be used in paleolatitude...

A área referente ao Neoproterozoico na Argentina é relativamente restrita e há considerável falta de dados sobre a exatidão da idade das rochas sedimentares locais e sobre a paleogeografia do ambiente de deposição. A migração aparente dos polos magnéticos, que define a posição das placas no tempo, é bem documentada para o Gondwana no período entre 550-500 Ma, porém há carência desses dados no intervalo entre 600-550 Ma e a análise paleomagnética da Formação Cerro Negro, Grupo La Providencia, Argentina, de idade ediacarana, pode contribuir para o conhecimento paleomagnético deste intervalo. Foram estudadas três coleções de rochas, uma de afloramento (CA) e dois testemunhos (TSE-13 e TA-21). Foram isoladas três componentes em cada conjunto de amostras, denominadas A, B e C. A componente A, de baixa estabilidade, das três coletâneas apresentaram grande dispersão dos dados e, por isso, resultados de estatística não confiáveis, com erros altos. A componente B, muito difundida, é considerada secundária, resultante de processos de remagnetização ocorridos entre o Permiano e o Triassico. Na coleção CA, a componente B, desbloqueada em temperaturas em torno de 350 °C, apresenta direção média em Dec: 356,2, Inc: -29,7 (n: 17 e α95: 9,3). Na coleção TSE-13, a componente B possui temperaturas de desmagnetização ≤350 °C, com direção média em Dec: 8,9, Inc: -37,4 (n: 21 e α95: 10,4). No testemunho TA-21, a componente B, de dupla polaridade, com temperaturas de desbloqueio ≤625 °C, possui direção média em Dec: 8,1, Inc: -50,7 (n: 46 e α95: 6,3). A componente C do poço TA-21, também constatada como secundária, com dupla polaridade e temperaturas de desmagnetização ≤675 °C, apresenta Dec: 12,2, Inc: -38,7 (n: 61 e α95: 4,7). Já a componente C da coleção TSE-13 foi a única componente isolada que carrega a magnetização característica das rochas, transportada por hematita (temperaturas entre...
Keywords: Paleomagnetismo; Rochas sedimentares; Paleografia; Argentina